Advanced Humidified Gas Turbine Cycle Concepts Applied to Micro Gas Turbine Applications for Optimal Waste Heat Recovery. (May 2017) - De Paepe, Ward; Carrerro, Marina Montero; Bram, Svend; Parente, Alessandro; Contino, Francesco
Abstract: Introduction of water in a micro Gas Turbine (mGT) has proven to be a very efficient way to introduce waste heat in the cycle. The injection of preheated water/steam in the mGT cycle will increase the efficiency of the cycle significantly. Different routes exist for water injection in an mGT cycle. Classical routes, like injection of steam/preheated water or the micro Humid Air Turbine (mHAT) cycle, where water is introduced in the cycle by means of a saturation tower, have shown to have high potential, however do not fully exploit the maximal potential for waste heat recovery. More advanced humidified gas turbine cycles exist on large scale, but these concepts have not yet been applied on mGT scale. In this paper, we study the impact of these different, more advanced, humidified gas turbine cycle concepts on the mGT performance. The different selected cycles – next to the classical Steam Injected Gas Turbine (STIG), injection of (preheated) water and the mHAT – were: mHAT-plus, Advanced Humid Air Turbine (AHAT) and the Regeneration EVAPoration cycle (REVAP ® ). Simulations indicated that humidifying the air of the mGT has a significant beneficial effect on the cycle performance, resulting in increased electrical power output and efficiency. Depending on the different used cycle layout, more waste heat could be recovered from the exhaust gas. The REVAP ® cycle with feedwater preheat was identified as the optimal cycle layout within the selected cycles. Using this concept, the stack temperature could be lowered to 53 °C, corresponding to an increase in electrical power output of 128.7 kWe with a maximal absolute efficiency increase of 6.9% compared to the dry cycle layout (100.1 kWe electrical power output and 35.1% efficiency).